ØªØ¹Ù"ÙŠÙ€Ù€Ù... Ø§Ù"Ù"ØºØ© Ø§Ù"Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù...Ø¯Ø±Ø³Ù€Ù€Ø© Ø§Ù"Ù...Ù€Ù€Ù€Ø§Ù"Ùƒ Ø§Ù"ØµÙ€Ù€Ù€Ø§Ù"Ø Ø§Ù"Ø¹Ù€Ù€Ø§Ù"ÙŠØ© Ø§Ù"Ø¥Ø³Ù€Ù"Ø§Ù...ÙŠØ© Ø§Ù"ØÙ€Ù€Ù€Ù€ÙƒÙˆÙ...ÙŠØ© Ø¨Ù€Ù"ÙƒØ³Ø¤Ù...Ø§ÙˆÙ‰ - Januar Hawani (Universitas Islam Negeri Ar-Raniry, 2014)
One of the obligations that must be undertaken by students of College of Islamic Studies (STAIN) Malikussaleh Lhokseumawe, is to study Arabic course. The problem encountered in teaching Arabic is the difference between curriculum applied from studentsâ€™ abilities. The purpose of this study is: to find out about the curriculum used in teaching Arabic at STAIN Malikussaleh LhokseumaweØŒ knowing the school's efforts to progress in teaching Arabic at STAIN Malikussaleh Lhokseumawe and find out the problems faced by the teachers in promoting learning Arabic in STAIN Malikussaleh Lhokseumawe. The results of this study are: (1) Teaching Arabic at STAIN Malikussaleh Lhokseumawe is using â€œAl-â€˜Arabiyyah Lak 1â€ dan â€œAl-â€˜Arabiyyah Lak 2â€. However, most teachers do not employ suitable methods and medias. Some students said that teachers do not use the media, but the board and textbooks. (2) The effort to improve learning Arabic at STAIN Malikussaleh Lhokseumawe requires teachers to use appropriate methods and media in teaching and learning. (3) The problems faced by teachers are quite related to teaching materials that do not match with studentsâ€™ ability. Furthermore, only few teachers who apply research methods and use of the learning media. Keywords: Keywords: